Information Systems for Patient Follow-Up and Chronic Management of HIV and Tuberculosis: A Life-Saving Technology in Resource-Poor Areas - Fraser, Hamish SF; Allen, Christian; Bailey, Christopher; Douglas, Gerry; Shin, Sonya; Blaya, Joaquin (JMIR Publications, 2007)
Background The scale-up of treatment for HIV and multidrug-resistant tuberculosis (MDR-TB) in developing countries requires a long-term relationship with the patient, accurate and accessible records of each patient's history, and methods to track his/her progress. Recent studies have shown up to 24% loss to follow-up of HIV patients in Africa during treatment and many patients not being started on treatment at all. Some programs for prevention of maternal-child transmission have more than 80% loss to follow-up of babies born to HIV-positive mothers. These patients are at great risk of dying or developing drug resistance if their antiretroviral therapy is interrupted. Similar problems have been found in the scale-up of MDR-TB treatment. Objectives The aim of the study was to assess the role of medical information systems in tracking patients with HIV or MDR-TB, ensuring they are promptly started on high quality care, and reducing loss to follow-up. Methods A literature search was conducted starting from a previous review and using Medline and Google Scholar. Due to the nature of this work and the relative lack of published articles to date, the authors also relied on personal knowledge and experience of systems in use and their own assessments of systems. Results Functionality for tracking patients and detecting those lost to follow-up is described in six HIV and MDR-TB treatment projects in Africa and Latin America. Preliminary data show benefits in tracking patients who have not been prescribed appropriate drugs, those who fail to return for follow-up, and those who do not have medications picked up for them by health care workers. There were also benefits seen in providing access to key laboratory data and in using this data to improve the timeliness and quality of care. Follow-up was typically achieved by a combination of reports from information systems along with teams of community health care workers. New technologies such as low-cost satellite Internet access, personal digital assistants, and cell phones are helping to expand the reach of these systems. Conclusions Effective information systems in developing countries are a recent innovation but will need to play an increasing role in supporting and monitoring HIV and MDR-TB projects as they scale up from thousands to hundreds of thousands of patients. A particular focus should be placed on tracking patients from initial diagnosis to initiation of effective treatment and then monitoring them for treatment breaks or loss to follow-up. More quantitative evaluations need to be performed on the impact of electronic information systems on tracking patients.